Psychological Distress, Fear and Coping Strategies During the Second and Third Waves of the COVID-19 Pandemic in Southern Germany - Elsayed, Mohamed; Schönfeldt-Lecuona, Carlos; Welte, Xenia Anna; Dardeer, Khaled Tarek; Kamal, Manar Ahmed; Abdelnaby, Ramy; Rudek, Markus A.; Riedel, Evelyne; Denkinger, Michael; Gahr, Maximilian; Connemann, Bernhard J.; Alif, Sheikh M.; et al. (Frontiers in Psychiatry, 2022)
Abstract Background: The COVID-19 pandemic has imposed enormous psychological discomfort and fear across the globe, including Germany. Objectives: To assess the levels of COVID-19 associated psychological distress and fear amongst Southern German population, and to identify their coping strategies. Methods: A cross-sectional survey using an online questionnaire was conducted in healthcare and community settings in the region of Ulm, Southern Germany. Assessment inventories were the Kessler Psychological Distress Scale (K-10), the Brief Resilient Coping Scale (BRCS), and the Fear of COVID-19 Scale (FCV-19S), which were valid and reliable tools. Results: A total of 474 Individuals participated in the study. The mean age was 33.6 years, and 327 (69%) were females. Most participants (n=381, 80.4%) had high levels of psychological distress, whereas only 5.1% had high levels of fear, and two-thirds of participants showed higher levels of coping. Moderate to very high levels of psychological distress were associated with being female, living alone, distress due to employment changes, experiencing financial impact, having multiple co-morbidities, being a smoker, increased alcohol use over the previous 6 months, contact with COVID-19 cases and healthcare providers for COVID-19-related stress. Individuals who were ≥60 years, lived with non-family members, had co-morbidities and visited a healthcare provider had higher levels of fear. Higher levels of education and income showed better coping amongst participants. Conclusion: Psychological distress was very high during the COVID-19 pandemic in Germany and associated with low levels of coping. This study identified vulnerable groups of people, who should be given priorities for addressing their health and wellbeing in future crisis periods.